Why the electoral college is bad for America - Edwards, George C. (New Haven, Conn. : Yale University Press, 2004)
"Americans currently choose their president through the electoral college, an extraordinarily complex mechanism that may elect the candidate who does not receive the most votes. In this book, George Edwards III argues that - contrary to what supporters of the electoral college claim - there is no real justification for a system that might violate majority rule." "Edwards finds that the electoral college does not protect the interests of small states or racial minorities, does not provide presidents with effective coalitions for governing, and does little to protect the American polity from the alleged harms of direct election of the president. In fact, the electoral college distorts the presidential campaign so that candidates ignore most small states and some large ones any pay little attention to minorities, and it encourages third parties to run presidential candidates and discourages party competition in many states." "Edwards demonstrates that direct election of the president without a runoff maximizes political equality and eliminates the distortions inn the political system caused by the electoral college."--Jacket.
How the electoral college works -- The electoral college and political equality -- Contingent elections -- The origins of the electoral college -- Protecting interests -- Maintaining cohesion -- Conclusion.
Includes bibliographical references (pages 169-189) and index.
Keywords: USA -- President; Electoral college -- United States; Presidents -- United States -- Election; Electoral college; Presidents -- Election; United States; Electoral college; USA; Electoral college; Nonfiction